Surgical Management of Chronic Pulmonary Aspergillosis in Africa: A Systematic Review of 891 Case - Bongomin, Felix; Olum, Ronald; Kwizera, Richard; Baluku, Joseph Baruch (Mycoses, 2021)
Chronic pulmonary aspergillosis (CPA) is an emerging fungal infectious disease of public health importance. We conducted a systematic review of studies reporting the outcomes of patients with CPA managed surgically in Africa. A search of Medline, Embase, Web of Science, Google Scholar and African Journals Online was conducted to identify studies indexed from inception to June 2021 that examined surgical management of CPA in Africa. All articles that presented primary data, including case reports and case series, were included. We excluded review articles. A total of 891 cases (557 males (62.5%), mean age 39.3 years) extracted from 27 eligible studies published between 1976 and 2020 from 11 African countries were included. Morocco (524, 59%) and Senegal (99, 11%) contributed the majority of cases. Active or previous pulmonary tuberculosis was reported in 677 (76.0%) cases. Haemoptysis was reported in 682 (76.5%) cases. Lobectomy (either unilateral or bilateral, n = 493, 55.3%), pneumonectomy (n = 154, 17.3%) and segmentectomy (n = 117, 13.1%) were the most frequently performed surgical procedures. Thirty (4.9%) cases from South Africa received bronchial artery embolisation. Empyema (n = 59, 27.4%), significant haemorrhage (n = 38, 173.7%), incomplete lung expansion (n = 26, 12.1%) and prolonged air leak (n = 24, 11.2%) were the most frequent complications. Overall, 45 (5.1%) patients died. The causes of death included respiratory failure (n = 14), bacterial superinfection/sepsis (n = 10), severe haemorrhage (n = 5), cardiopulmonary arrest (n = 3) and complications of chronic obstructive pulmonary disease (n = 3). The cause of death was either unknown or unspecified in 9 cases. We conclude that surgical treatment had very low mortality rates and maybe considered as first-line management option in centres with experience and expertise in Africa.
Keywords: Africa, pulmonary aspergilloma, surgical management